Effect of creep on the Bauschinger effect in a polycrystalline austenitic stainless steel. (February 2017) - Hu, J.N.; Cocks, A.C.F.
Abstract: A combined thermodynamic/kinetic approach is adopted to derive the climb-controlled recovery of dislocation junctions on individual slip planes in a material during creep when dislocation core diffusion is the rate controlling kinetic process. The model is used in an integrated multi-scale crystal plasticity/creep self-consistent framework to evaluate the effect of creep pre-strain on the Bauschinger effect in a polycrystalline austenitic stainless steel. The model predictions are in good agreement with experimental findings of the effect of tensile creep on the subsequent low temperature response in tension and compression and on the development of residual stresses determined from neutron diffraction studies. Graphical abstract: